Facilitating Forgiveness in Organizational Contexts: Exploring the Injustice Gap, Emotions, and Expressive Writing Interventions - Barclay, Laurie J. (Journal of business ethics, 2016)
Despite the numerous benefits associated with forgiveness, many individuals find it difficult to forgive. This is especially true in organizations, where forgiveness is rare and can be under-valued. Across two studies, we explore how to facilitate forgiveness within organizational contexts and in the aftermath of workplace unfairness. We examine whether individuals can reduce the “injustice gap” that can be created by violations and enhance forgiveness through expressive writing interventions—guided writing techniques that can be self-administered. Participants wrote about their reactions to a fictional scenario (Study 1; N = 155) or an actual workplace experience (Study 2; N = 96). Results indicate that expressive writing was associated with higher reported perceived resolution. Whereas negative emotions mediated this relationship in Study 1, positive emotions and perceived injustice mediated this relationship in Study 2. Perceived resolution also mediated the relationship between expressive writing and forgiveness. Theoretical, methodological, and practical implications are discussed.